Cognitive analytic team formulation: learning and challenges for multidisciplinary inpatient staff. Issue 2 (2nd July 2019) - Stratton, Rose; Tan, Ranil
Abstract : Purpose: The purpose of this paper is to understand staff experiences of cognitive analytic team formulation, within an inpatient unit for women with a diagnosis of personality disorder. Design/methodology/approach: In total, 16 staff completed an online questionnaire, rating their views on how helpful formulation sessions had been in regards to ten domains. Following this, six staff participated in semi-structured interviews exploring their experiences of the process and impact of cognitive analytic team formulation. Transcripts were analysed using thematic analysis. Findings: Responses from questionnaires indicated the general process of team formulation was helpful across each domain. Interviews highlighted benefits such as an increased capacity to think and work relationally. This was impacted upon by staff's confidence in using the model and the practicalities of attending sessions. Practical implications: Team formulation has been described as the facilitation of a group of professionals to create a shared understanding of service-users' difficulties. Team formulation continues to demonstrate benefits for staff working within complex mental health. The challenges of this are considered, however overall, a cognitive analytic framework seems to offer staff the opportunity to integrate learning from a service-user's history, and current relational difficulties, in a way that develops reflective capacity and informs intervention. Originality/value: Limited research has explored the theoretical models underpinning team formulation, and the impact for staff learning and practice. The current study develops previous work by specifically focussing on the contribution of cognitive analytic theory to team formulation.